(untitled) (Fiep Bulletin - online, 2014)
When dealing with high-performance athletes, small details can make a difference to the victories happen. Thus, the development of grip strength must be present in the planning of technicians and trainers, as well as its form of assessment. This research aimed to determine the levels of handgrip strength in boxing practitioners, beginners and advanced, male, between 18 and 28 years. The sample consisted of 61 individuals with mean age 23.7±3.1 years and 30 beginners (GI) and 31 advanced (GA), class participants boxing premises of a health Joinville - SC at least 3 times per week. Protocols were used standardized assessment of manual dynamometry, circumference, body weight and height of Fernandes Filho (2000). The main results of the comparative of the absolute strength of the right hand group Beginner (GI) showed values ??of 49.47±9.16 kg and the advanced group (GA) obtained lower values ??48.68±6.60 a difference of 0.8 kg of absolute strength (p = .70). The absolute strength of the left hand of GI showed values ??of 48.25+9.33 kg and GA obtained the values ??of the hand strength of 47.52 ±7.77 kg showing a difference of .7 kg more of strength absolute (p = .74) for the hand of GI In both cases confirming no statistical difference between the groups. With this study it was possible to identify different values ??between the groups, though not formalized a significant difference. It should, however, seek new studies that are more efficient in finding information and thus, we suggest that the groups are categorized not only by practice time.